Excellent Accreditation Design in High School - Furtasan Ali Yusuf; Basrowi (JTP - Jurnal Teknologi Pendidikan, 2021)
The purpose of this study is to analyze the strategy for achieving superior accreditation of higher education institutions (excluding study programs). The research design used is a descriptive-quantitative study. The research was conducted at Bina Bangsa University during the institutional accreditation field assessment (AL) on August 13-14, 2021. Data analysis used nine criteria for university accreditation assessment assessed by BAN-PT. The results of the study found that the design of superior accreditation in higher education can be done by: 1) compiling a Self Evaluation Report (LED) that is congruent with the Higher Education Performance Report (LKPT) without any discrepancies with each other, 2) universities need to form institutions and carry out quality assurance seriously, 3) maximize the value of each item of accreditation fromCriteria A, B, C1--C9, and criteria D; 4) trying as much as possible to fulfill all the physical evidence needed to meet each of the existing criteria, 5) trying to provide answers to assessors during interview sessions both to the Foundation, Chancellor, middle leaders, lecturers, students, employees, alumni, cooperation partners and users .The novelty of the research is shown from the superior accreditation design related to the difficulty in meeting the accreditation criteria for colleges and study programs. This study suggests that every university should continue to make improvements in order to obtain superior accreditation by implementing good design.